MADRASAH AS AN INSTITUTION OF ISLAMIC EDUCATION AND SOCIAL CHANGE - Maryati, Sri; Lestarika, Lestarika; Idi, Abdullah; Tri Samiha, Yulia (LP2M IAI Al-Khairat Pamekasan, 2023)
Madrasah is one of the Islamic educational institutions in Indonesia that integrates Islamic education and general education. The birth of madrasah educational institutions is a desire to change existing institutions. The development of madrasah is in line with efforts to adapt and with the existing education system in Islamic boarding schools with general education. Madrasah plays a strategic role in responding to the impact of globalization, creating students with character who can have a strategic role in making social changes that positively impact society. Madrasah, as an educational institution, has a function to carry out social change: (1) develop a cultural analysis of traditional institutions, (2) make changes or modifications in traditional education, (3) make more fundamental changes to traditional institutions that are no longer by the times. Madrasah serves as a place for the process of social change to change whose progress is forward as a centre for shaping and developing the progress of students.